Pengaruh Zakat Infak Sedekah (ZIS) dan Indeks Pembangunan Manusia (IPM) Terhadap Pertumbuhan Ekonomi di NTB Tahun 2018-2022 - Virda, Virda noviyanti; Ismayadi (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2024)
improve people's standard of living and encourage distribution and changes in income. In economic growth, there are several factors that influence growth itself. This study aims to analyze the effect of ZIS (Zakat, Infak and Sedekah) and IPM (Human Development Index) on the economic growth of NTB Province (West Nusa Tenggara) in 2018-2022. The method used is the classical assumption test and multiple regression analysis with the help of the SPSS version 26.0 program to obtain a comprehensive picture of the relationship between one variable and another. The sample in this study consisted of 10 cities/regencies in NTB Province during 2018-2022. The data used in this study is secondary data from the National Zakat Agency (BAZNAS) of NTB Province, for data on the distribution of ZIS funds, IPM, and economic growth sourced from the Central Statistics Agency of NTB Province from 2018-2022. The results of the study indicate that the ZIS variable does not have a significant effect on Economic Growth partially while the HDI has a significant effect on Economic Growth partially. The results of the simultaneous regression analysis obtained that the estimated linear regression model is feasible to be used to explain the effect of ZIS and HDI on Economic Growth.